Short message service (SMS)-based intervention targeting alcohol consumption among university students: study protocol of a randomized controlled trial - Thomas, Kristin (Trials, 2017)
BACKGROUND: Despite significant health risks, heavy drinking of alcohol among university students is a widespread problem; excessive drinking is part of the social norm. A growing number of studies indicate that short message service (SMS)-based interventions are cost-effective, accessible, require limited effort by users, and can enable continuous, real-time, brief support in real-world settings. Although there is emerging evidence for the effect of SMS-based interventions in reducing alcohol consumption, more research is needed. This study aims to test the effectiveness of a newly developed SMS-based intervention targeting excessive alcohol consumption among university and college students in Sweden. METHODS: The study is a two-arm randomized controlled trial with an intervention (SMS programme) and a control (treatment as usual) group. Outcome measures will be investigated at baseline and at 3-month follow up. The primary outcome is total weekly alcohol consumption. Secondary outcomes are frequency of heavy episodic drinking, highest estimated blood alcohol concentration and number of negative consequences due to excessive drinking. DISCUSSION: This study contributes knowledge on the effect of automatized SMS support to reduce excessive drinking among students compared with existing support such as Student Health Centres. TRIAL REGISTRATION: ISRCTN.com, ISRCTN95054707. Registered on 31 August 2016. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s13063-017-1898-3) contains supplementary material, which is available to authorized users.